Groundwater in Southwestern Algeria: An Essential Heritage and Keys to Development - MERZOUGUI, Touhami; Cherif, Rezzoug; et, Remini Boualem (Journal of Water, 2023)
A regional overview describes groundwater resources in Southwestern Algeria, assessing challenges and strategies for sustainable development under climatic and demand pressures.
Keywords: UroscopyGroundwater; environment; summer; dry season.